O papel das associações e cooperativas no desenvolvimento das empreendedoras ceramistas: um estudo multicasos no Brasil e na Nicaragua - Patriarca, Maria Clarice Silva (2013)
This research aims to verify the role of cooperatives and associations in the development of entrepreneurial ceramists in Brazil and Nicaragua. Therefore, two associations in Brazil and two cooperatives in Nicaragua were selected. These organizations were chosen owing to the similiarities between them. The research was developed as a multiple case study, and the interviews were conducted through semi-structured questions. The interviewers were free to add any information they thought necessary. We identified eight general categories, which were reduced to three main categories. The data obtained were analyzed using content analysis, and as a result, among other things, may verify the impacts generated by the potters participation in associations and cooperatives, from personal, family and social aspects, in addition to issues involving the community in which they live. Also verified was the need for dissemination and the development of public policies with the final objective being to publicise the artisans, and the different characteristics between the focus given to participation in associations, in both Brazil, and cooperatives in Nicaragua. Talk in Brazil indicates the emphasis placed by the associated issues in relation to social life, and talk in Nicaragua, suggests a greater concern about financial issues. Perhaps these characteristics are related in the end, to the type of organization chosen to unite the groups in the two countries. The contributions of this work are generated by the amplification of the literature related to women entrepreneurship and also by launching a different look at the reality of enterprising potters, due to their involvement with cooperatives and associations, in relation to aspects of personal, family, economic and social. Finally, this work presents possible topics for future research, including those related to further studies that take into account the concept of entrepreneurship defined here-in, studies that deepen the understanding of the psychological impacts generated by the entrepreneurship of women involved with subsistence activities, and furthermore the possibilities of studying the actions of training and development of public policies aimed at this audience.